Climate action’s work on climate information services - Ramirez Villegas, Julian; Ghosh, Aniruddha (2024)
This presentation offers a comprehensive overview of the Climate Action research lever, highlighting its mission, strategic approach, and key contributions. It showcases examples from our diverse research portfolio, traces the historical evolution of our efforts, and outlines our geographical reach and identity. As climate information services become a key priority in many new climate action investments globally, the presentation emphasizes our commitment to advancing impactful climate solutions, fostering resilience, and leveraging cutting-edge research to address global challenges